The locally acting glucocorticosteroid budesonide enhances intestinal sugar uptake following intestinal resection in rats. Issue 2 (1st February 2003) - Thiesen, A; Wild, G E; Tappenden, K A; Drozdowski, L; Keelan, M; Thomson, B K A; McBurney, M I; Clandinin, M T; Thomson, A B R
Abstract : Background and aims: Locally and systemically acting corticosteroids alter the morphology and transport function of the intestine. This study was undertaken to assess the effect of budesonide, prednisone, and dexamethasone on sugar uptake. Methods: Adult male Sprague Dawley rats underwent transection or resection of 50% of the middle portion of the small intestine, and in vitro uptake of sugars was measured. Results: The 50% enterectomy did not alter jejunal or ileal uptake of glucose or fructose. Prednisone had no effect on the uptake of glucose or fructose in resected animals. In contrast, in resected rats budesonide increased by over 120% the value of the jejunal maximal transport rate for the uptake of glucose, and increased by over 150% ileal uptake of fructose. Protein abundance and mRNA expression of the sodium dependent glucose transporter in brush border membrane (SGLT1), sodium independent fructose transporter in the brush border membrane (GLUT5), sodium independent glucose and fructose transporter in the basolateral and brush border membranes (GLUT2), and Na + /K + ATPase α1 and β1 did not explain the enhancing effect of budesonide on glucose or fructose uptake. Budesonide, prednisone, and dexamethasone reduced jejunal expression of the early response gene c-jun. In resected animals, expression of the mRNA of ornithine decarboxylase (ODC) in the jejunum was reduced, and corticosteroids reduced jejunal expression of the mRNA of proglucagon. Conclusions: These data suggest that the influence of corticosteroids on sugar uptake in resected animals may be achieved by post translational processes involving signalling with c-jun, ODC, and proglucagon, or other as yet unknown signals. It remains to be determined whether budesonide may be useful to stimulate the absorption of sugars following intestinal resection in humans.